Association between Age and the 28-Day All-Cause Mortality in Tuberculosis Complicated by Sepsis in ICU Patients: A Retrospective Cohort Study [Response to Letter] - Cui K; Mao Y; Feng S; Luo H; Yang J; Xu R; Bai L (Infection and Drug Resistance, 2024)
Kunping Cui,1,* Yi Mao,2,* Shuang Feng,3 Haixia Luo,2 Jiao Yang,2 Ruyi Xu,1 Lang Bai1 1Center of Infectious Diseases, West China Hospital of Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 2Intensive Care Unit, Public Health Clinical Center of Chengdu, Chengdu, Sichuan, 610000, People’s Republic of China; 3Ultrasonic Medicine, Public Health Clinical Center of Chengdu, Chengdu, Sichuan, 610000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lang Bai, Center of Infectious Diseases, West China Hospital of Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China, Tel +86-18980602254, Email pangbailang@163.com